Horizontal Gene Transfer From Bacteria and Plants to the Arbuscular Mycorrhizal Fungus Rhizophagus irregularis - Li, Meng; Zhao, Jinjie; Tang, Nianwu; Sun, Hang; Huang, Jinling (Frontiers in Plant Science, 2018)
Arbuscular mycorrhizal fungi (AMF) belong to Glomeromycotina, and are mutualistic symbionts of many land plants. Associated bacteria accompany AMF during their lifecycle to establish a robust tripartite association consisting of fungi, plants and bacteria. Physical association among this trinity provides possibilities for the exchange of genetic materials. However, very few horizontal gene transfer (HGT) from bacteria or plants to AMF has been reported yet. In this study, we complement existing algorithms by developing a new pipeline, Blast2hgt, which efficiently screens for putative horizontally derived genes from a whole genome. Genome analyses of the glomeromycete Rhizophagus irregularis identified 19 fungal genes that have been transferred between fungi and bacteria/plants, of which seven were obtained from bacteria. Another 18 R. irregularis genes were found to be recently acquired from either plants or bacteria. In the R. irregularis genome, gene duplication has contributed to the expansion of three foreign genes. Importantly, more than half of the R. irregularis foreign genes were expressed in various transcriptomic experiments, suggesting that these genes are functional in R. irregularis. Functional annotation and available evidence showed that these acquired genes may participate in diverse but fundamental biological processes such as regulation of gene expression, mitosis and signal transduction. Our study suggests that horizontal gene influx through endosymbiosis is a source of new functions for R. irregularis, and HGT might play a potential role in the evolution and symbiotic adaptation of this arbuscular mycorrhizal fungus.